Postępowanie w nadciśnieniu tętniczym – aktualizacja zaleceń Europejskiego Towarzystwa Nadciśnienia Tętniczego - Gaciong, Zbigniew; Wilczko, Justyna (Przewodnik Lekarza/Guide for GPs, 2010)
An overview of recent findings from major clinical trials in hypertension (till July 2010) along with 2009 reappraisal of guidelines of European Society of Hypertension is presented as a practical overview of management of hypertension including threshold and goal blood pressure in specific situations, choice of antihypertensive medications, indications for treatment of concomitant risk factors.